PENYELESAIAN SENGKETA PENOLAKAN PENCAIRAN DANA DEPOSITO PEWARIS OLEH AHLI WARIS PADA BANK NIAGA (Studi Putusan Nomor: 135/Pdt.P/2022/PN.Tjk) - Erlina B; Okta Ainita; Dendy Francysco Sinurat (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2022)
This study aims to find out the procedure for disbursing funds or withdrawing funds from heirs based on the Study Decision Number: 135/pdt.P/2022/PN TJK and to find out the court's decision in the process of disbursing deposit funds based on the Study Decision Number: 135/pdt.P/ 2022/PN TJK. Because Bank Niaga Teluk Betung, Bandar Lampung City, will not disburse the funds of customers who have died to their heirs before there is a final decision from the court. The approach used in this study is a normative juridical approach and an empirical juridical approach to obtain correct and objective research results. Then for the data analysis process, the data that has been systematically compiled is analyzed in a qualitative juridical manner, namely by providing an understanding of the data in accordance with the facts obtained in the field, so that it is truly from the subject matter. in hand and arranged in sentence by sentence. scientific and systematic in the form of answers to problems based on research results. The results of the study explain that the Bank applies the precautionary principle in disbursing customer funds that have died based on the Standard Operating Procedure (SOP) of the bank. The bank's responsibility for negligence is to apply the precautionary principle of the bank in disbursing customer funds that have died, namely by compensating or returning the funds that have been sought.